Micromorphology and clast microfabrics of subglacial traction tills at the sea cliff Dwasieden: evidence of polyphase syn- and post-depositional deformation - Brumme, Johannes; Hüneke, Heiko; Phillips, Emrys (DEUQUA Special Publications, 2019)
A detailed thin-section-based micromorphological and microstructural study of the glacial diamicts exposed at the sea cliff of Dwasieden (M1, M2, M2) has revealed that all units can be related, in their entirety or in several parts, to subglacial conditions during the repeated readvance of the Scandinavian Ice Sheet. These readvances are characterised by polyphase deformation of the diamicts resulting in the development of ductile and brittle structures and localised water-escape structures. Subsequent alteration under periglacial conditions has been documented for the chalk and till units M1 and M2.